Maracas Bay - Thomas, H.O. (H.O. Thomas, 2009)
Maracas Bay, Trinidad popular north coast beach, located about half an hour from the capital, Port of Spain.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beachgoers--Trinidad and Tobago; Beaches--Trinidad and Tobago; Leisure--Trinidad and Tobago; Bays--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Maracas Bay